The theoretical discourse of the “national interest” concept: comparative analysis (International relations and international law Journal, 2021)
The article examines the principles of one of the theory of international relations – the theory of political realism – on the example of the works by Reinhold Niebuhr and Hans Morgenthau. In the history of the development of theories of international relations, the theory of political realism was the first to analyze the concept of “national interest” by and large. The protection of national interest is one of the main directions in ensuring state security. The supporters of political realism believe that any state should not be unserious about its national interests. The national interests of countries determine the nature of relations between countries. The national interests are the stable basis of international relations.The formation and development of national relations is influenced by the geographic location of the country, the level of its political, social, economic, and cultural development. Reinhold Niebuhr believes that the nation-state is a community with a specific mission. It is a society that takes on obligations to its citizens, to the outside world. The formation of a nation-state is influenced by such factors as the confidence of citizens in the country within the indicated transcendental activities of the state and the devotion of citizens to their country. He also believes that there are pluralistic, henotheistic and monotheistic types of citizens’ trust in their country. Hans Morgenthau views international relations as an arena of contradictions between countries.The aim of the study is to conduct a comparative analytical analysis of the theoretical discourse of the concept of “national interest” found in the literature. The main areas of research are updating existing ideas about the concept based on new geopolitical realities, considering the theoretical discourse of national interests by providing an expert definition of the concept. The scientific and practical significance of the work lies in the importance of the theoretical discourse of the initiative actors of the XXI century in the active protection of their national interests. The comparative analytical method was used as a research method, since today, due to the relevance of the topic, actors are actively using a new approach. The historical results also show the relevance of the factor through practical guidance to experts and policy makers, depending on the main findings of the study, analysis and concept. At the same time, decision-makers have not lost their relevance not only in the relevance of modern ideas, but also in the conceptual ideas of theorists used in the article. The importance of research is a small contribution to the social sciences and humanities through the theoretical discourse of demonstration analysis. The practical significance of the results of the work lies in the perception of the academic environment and persons making practical decisions as a recommendation.Key words: national interests, political realism, theory of international relations.